Rolling window regression of δ13C and δ18O values in carbonate sediments: Implications for source and diagenesis. (25th September 2019) - Oehlert, Amanda M.; Swart, Peter K.
Abstract: Diagenetic alteration can produce, modify or erase significant biogeochemical information recorded in carbon and oxygen (δ 13 C and δ 18 O) values of marine carbonates throughout geological time. Understanding the type and extent of alteration experienced by a carbonate deposit can improve sedimentological and geochemical interpretations of events in Earth history. In this study, we present a new application of a statistical approach to aid in the identification and interpretation of sedimentological surfaces in a shallow marine carbonate sequence using a rolling window regression (RWR) analysis. RWR analysis evaluates the degree of covariation between two records and how it changes through time. Geological application of this statistical technique permits a new perspective on the fine scale variability in carbon and oxygen isotope records and the processes that generate them and provides a complementary tool for sedimentological interpretations. In this study, we apply RWR to δ 13 C and δ 18 O values from the Clino drilled into the western margin of Great Bahama Bank, a core that has been extensively altered by diagenetic processes, within the vadose, phreatic and marine burial zones. This core penetrates 676 m of shallow marine to deeper slope deposits and contains a variety of both sedimentological and diagenetic events, including facies transitions, subaerial exposure surfaces, marine hardgrounds, firmgrounds and periods of reduced sedimentation rate. Using more than 1, 200 analyses of paired δ 13 C and δ 18 O values, we have applied a RWR analysis to evaluate how the correlation between these two proxies changes at scales of 10, 30 and 100 m. The results of this study highlight the dynamic evolution of correlations between δ 13 C and δ 18 O values within diagenetic zones and in association with diagenetic surfaces and provide context for interpreting covariance in δ 13 C and δ 18 O values from the geological record. Abstract : In this study, rolling window regression analysis was employed for the identification of sedimentological and diagenetic surfaces using records of stable carbon and oxygen isotopes in shallow marine carbonates from the Bahamas. The statistical analysis is complemented by the development of a new interpretive framework for evaluating the physical, chemical, and biological mechanisms that generate diagenetic alteration associated with marine hardgrounds, periods of low sedimentation rate, and subaerial exposure surfaces.